Film Theory : An introduction through the senses - Elsaesser, Thomas; Hagener, Malte (New York, London : Routledge, 2010)
Introduction : film theory, cinema, the body and the senses -- Cinema as window and frame -- Cinema as door : screen and threshold -- Cinema as mirror and face -- Cinema as eye : look and gaze -- Cinema as skin and contact -- Cinema as ear : acoustic and space -- Cinema as brain : mind and brain -- Conclusion : digital cinema : the body and the senses refigured?
What is the relationship between cinema and spectator? This title employs this question to guide students through the major film theories, from the classical period onwards.
boek